AVALIAÇÃO DOS SERVIÇOS DE ATENÇÃO PRIMÁRIA À SAÚDE EM SÃO JOSÉ DE RIBAMAR-MA. - COSTA, Mannasses Araújo (2019)
The Primary Health Care (PHC) configures the preferential entry door of users of a health system for all new needs and problems and has a strategic character in the structuring of actions. As a care model, it is usually represented by ambulatory services directed to respond to the most common health needs of a population. In order to understand the guidelines of PHC, Barbara Starfield proposed the concept of essential attributes (access of first contact, longitudinality, comprehensiveness and coordination of care) and derivatives (family orientation, community and Cultural competence). The evaluation of the quality of PHC is measured from the presence and extent of the attributes. The present study evaluated the quality of services in the Family Health Strategy of São José de Ribamar-MA from the perspective of 386 users and 73 professionals. Data were collected through the Primary Care Assessment Tool (PCATool-Brazil), which has versions for adult users and children and health professionals. In the professionals' perception, the result was satisfactory (score ≥ 6.6) in all attributes evaluated, except for first contact access. However, this perspective differs when analyzing the results of these services from the perspective of the users, the performance was unsatisfactory in almost all attributes. The divergences found in the results among the study subjects reveal that the services offered still do not meet all the health demands of the population in this level of care of the municipality. The managers and professionals should develop the methods of assessing the health situation and present means that provide changes in the work process of the teams against the unsatisfactory performance presented in almost all attributes from the perspective of users.